Automated addition of fault recovery to cyber-physical component-based models - Bonakdarpour, Borzoo; Lin, Yiyan; Kulkarni, Sandeep (Proceedings of the ninth ACM International Conference on Embedded Software, 2011)
In this paper, we concentrate on automated synthesis of fault recovery mechanism for fault-intolerant component-based models that encompass a cyber-physical system. We define the notion of fault recovery for cyber-physical component-based models. We also present synthesis constraints that preserve the correctness and cyber-physical nature of a given fault-intolerant model under which recovery can be added. We show that the corresponding synthesis problem is NP-complete and consequently introduce symbolic heuristics to tackle the exponential complexity. Our experimental results validate effectiveness of our heuristics for relatively large models.